The Relevance of Business Process Reengineering on Customer Care in the Banking Sector; A case study of CAL Bank Limited - Angorkor, Naa Tsakle Sophia (2017)
A thesis submitted to the School of Business, Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfillment of requirements for the award of Masters in Business Administration.